Do local public finances influence the economic growth of cities? The case of the 324 cities of the Tarn Department (France) - Olivier Thomas (European Regional Science Association (ERSA), 2004)
This paper aims at questioning the link between local finances and the economic dynamism of cities. This issue is based on the frequently stressed cases (by the media) of uncontrolled expenses of cities, increased level of local taxes and negative effects on local economics. This situation has been experimented in the cities of Briançon, Angoulême, and even in the little village of Eyne (Eastern Pyrenees) which had the biggest level of debt per inhabitant of the whole Europe in the beginning of the nineties. Therefore, as a starting point, the lack of neutral link between urban management and local attractive power of cities will be assumed. The relevance of the following assumptions will be considered : - assumption n°1 : the choice of the financial way to manage a city would positively influence economic dynamism, provided it would express the agreement with a “budgetary orthodoxy convention”.- assumption n°2 : conversely, local public management, insofar as it is based (notably) on debts and refers to what could be called “keynesian convention” would negatively influence the attractive power of cities.Thus, everything else equal, the more a city would be granted with important saving resources, the more it could afford to finance it own investments (or increased investments with a given rate of self-financing), the less financial expenses would lessen the functioning resources of the following year, etc … Moreover, a healthy financial management would improve the probability of a city to attract households and firms : if debts and local taxes can be restricted to a law level (in respect to the national average level, to the one of close competing cities …), then this law yearly increase of local taxes would not seem to shackle the dynamics of locations within a given city. The empirical part of this paper deals with the test of the relevance of the previous assumptions. Our sample is composed with all the 324 cities of the French Department of Tarn. The specific features of this sample are : the important number of statistical observations, the fact that all the cities of a local level, between metropolitan areas and Regions, are considered, the diversity of environments (rural, urban, agriculture, industry, dynamic or depressed industrial sectors), high of low proximity with an European metropolitan area (Toulouse), The attractive power of Tarn cities will be estimated by the increase (or decrease) of population. The assumptions will be tested thanks to ordinary least square regressions, and factor analysis. The database includes budgetary variables (budgets of cities, resources, expenses, savings, fiscal wealth, debts, investments, …), fiscal variables (local taxes, income tax, …) and also distances from each city to Toulouse, expressed in kilometres and in time. The conclusions will be detailed in terms of local planning, by comparing the impact of distance to fiscal “fixed” expenses.
Keywords: 330